Sintering of tin oxide processed by slip casting - Garcia dos Santos, Iêda Maria; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Leite, Edson Roberto (Elsevier, 2000)
Sintering of SnO 2 compacts, obtained through slip casting, was studied by means of dilatometry, Hg porosimetry, scanning electron microscopy, and density measurement (Archimedes method). Sintering is strongly influenced by the green microstructure. Moreover, the sintering mechanisms are not dependent on the slurries' solid content up to 50% of solids in volume. Above this value, agglomerates are formed, leading to differential sintering inside and among the agglomerates. Another important point is the reduction of the temperature of maximum shrinkage rate when compared to tin oxide processed by isostatic pressing. This reduction is more accentuated when ammonium hydroxide is added to the suspension. (C) 2000 Published by Elsevier Science Ltd. All rights reserved.

Sintering of SnO 2 compacts, obtained through slip casting, was studied by means of dilatometry, Hg porosimetry, scanning electron microscopy, and density measurement (Archimedes method). Sintering is strongly influenced by the green microstructure. Moreover, the sintering mechanisms are not dependent on the slurries' solid content up to 50% of solids in volume. Above this value, agglomerates are formed, leading to differential sintering inside and among the agglomerates. Another important point is the reduction of the temperature of maximum shrinkage rate when compared to tin oxide processed by isostatic pressing. This reduction is more accentuated when ammonium hydroxide is added to the suspension.
Keywords: Microstructure-final; Porosimetry; Sintering; Slip casting; SnO 2; Density measurement (specific gravity); Hot isostatic pressing; Metal casting; Porosity; Reduction; Scanning electron microscopy; Shrinkage; Archimedes method; Dilatometry; Green microstructure; Tin oxide; Tin compounds; casting; ceramics; porosity; sinter